Does WTO membership make a difference at the extensive margin of world trade? - Gabriel Felbermayr; Wilhelm K. Kohler (Center for Economic Studies and ifo Institute (CESifo), 2007)
In his seminal paper, Rose (2004) concluded from a gravity-type study of bilateral trade that the GATT/WTO does not play a strong role in encouraging trade. Rose looks at countries where the amount of trade was positive to start with (intensive margin). In this paper, we present a corner-solutions version of the gravity model of bilateral trade which explains zero trade and leaves room for WTO membership to promote trade at the extensive margin of trade. Relying on a Tobit estimation approach, we find that WTO membership has promoted world trade to a larger extent than Rose's results seem to indicate.
Keywords: F12; F13; 330; WTO-Beitritt; Außenwirtschaft; Weltwirtschaft; Schätzung; Welt